Self-realization as a form of manifestation of the abilities of teachers of innovative schools - Кудайбергенева, К.С.; Булакбаева, Мейрамгуль; Боранкулов, Е.К. (Pedagogy and Psychology, 2024)
The article deals with the problems of self-realization of one’s own capabilities of a creative person. The essence of self-realization has analyzed based on existential, immanent and active approaches and value orientations of a person’s individual free choice of a life path. On the basis of the universal principle of determinism, where a person is considered as "a whole system of internal conditions", a conceptual position of self-realization is proposed: - self-realization as an experience in relation to reality; self-realization as a goal in relation to the possibility; self-realization as a manifestation of the possibility in relation to the innovation movement, as well as a model of self-realization, reflecting the relationship of the past, present and future through experience, opportunities, innovative activity. Basis on empirical analysis, methodological directions for the study of self-realization based on an individual and activity approach are determined as a manifestation of practical identity, as an innovative challenge with new and alternative ways of activity, as an experience in the self-government system of socio-pedagogical transformations. The features of the experiment are noted, which are aimed not only at studying some kind of reality, but also at the formation of a certain life situation in conditions of free self-expression, and the meaning is not in “achieving the goal”, but in the realization of creative abilities. The technology of generating problem situations in the joint activity of the subjects and the experimenter has presented.